Macro-benthic diversity in relation to biotic indices in Song river at Dehradun, India - D. S. Malik; Umesh Bharti; Pawan Kumar (Environment Conservation Journal, 2010)
The composition and abundance of benthic animals are commonly used as bio-indicators to determine the impact of pollution on physico-chemical integrity of surface waters and changing pattern of biotic characteristics of lentic and lotic system. The benthos serves as a link between primary producers, decomposers and higher trophic level. Song river is a spring fed hill stream originated from different small rivulets of lesser Himalayan mountainous ranges at Garhwal region of Uttarakhand. The study was carried out from 2006-2008, the water samples were collected from three different sites in a stretch of about ten kilometres from Song river. All taxa were identified to species/genus level with the help of identification keys. The 5 faunal groups and 19 genera were observed at three different stations in the Song river. At all three sites, Tubifex was the dominant genera among Oligochaeta. Among polychaeta, Namalycastic indica, Napthys polybranchia, Napthys oligobrunchia species were reported at all above three different sites of Song river. Biotic indices indicated moderate pollution in the water quality of upstream and down stream water. The CCME (Canadian Council of Minister of Environment) water quality index (2001) showed marginal range of pollution in the river. The abundance of pollution tolerant organisms indicated the downstream site is receiving nutrient-rich urban runoff containing little or no toxins substances.